A novel flameless oxidation and in-chamber melting system coupled with advanced scrubbers for a laboratory waste plant. (1st May 2021) - Lin, Sheng-Lun; Wu, Jhong-Lin; Lin, Kuang C.; Wu, Han; Guo, Zhefeng; Tu, Chun-Wei
Highlights: Flameless oxidation is used for an ultralow-emission waste treatment process. A multi-burner system economically achieved the flameless oxidation. Integrated process can save 24.4–48.7% auxiliary diesel and natural gas. Regulated pollutant and PAH emissions were obviously reduced by new system. Bottom ash vitrification took place in combustion unit to save extra energy. Integrated system solved the corrosion issue found in the previous studies. Abstract: This is the first study integrate the flameless oxidation (FO) and in-chamber melting (ICM) processes in a primary chamber of a laboratory waste incinerator to improve energy and emission performances. Two liquid burners created a twin-cyclonic fluid field that achieved the FO and ICM in the same chamber. The first cyclone provided a well-mixed and lower temperature FO to reduce auxiliary diesel consumption, NOx and PM emissions by 25.8%, 30.9%, and 79.2%, respectively, from the original system. The hot gases produced by FO enhance the ICM process and transformed the bottom ashes to stabler slags, in turn meeting the regulations for nonhazardous wastes. The other cyclone enhanced the drying and water–gas shift reaction in the drying zone by recirculating the CO and enthalpy from FO and ICM. Eventually, the residual CO, hydrocarbons, and H2 were sent to the secondary chamber for further oxidation. A computational fluid dynamic simulation supported the fluid field assumption posed in this study. Moreover, advanced scrubbers were employed after thermal treatments to reduce HCl and SO2 by 81.8% and 38.8% and further retarded the corrosion rate in the baghouse supporting cage by 87.7%. The precursors of condensable particulate matter were reduced by condensation and finally removed in the baghouse. Nevertheless, the emissions of the high- and mid-molecular-weight polycyclic aromatic hydrocarbons were greatly reduced by 60.8–93.1% and 80.2–99.9%, respectively. Consequently, the new system reduced annual emissions by 40.7–87.6% and operating costs by 41.5%, allowing recovery of the remodification investment in 20.5 months.